1998
DOI: 10.1159/000024514
|View full text |Cite
|
Sign up to set email alerts
|

UCN-01, a Protein Kinase C Inhibitor, Inhibits Endothelial Cell Proliferation and Angiogenic Hypoxic Response

Abstract: Angiogenesis is required for tumor formation and growth; inhibition of angiogenesis is a promising new approach in cancer therapy. UCN-01, a protein kinase C (PKC) inhibitor, induces growth arrest and apoptosis in cancer cells and was recently introduced in a phase I clinical trial. We demonstrate that UCN-01, at concentrations lower than those necessary to inhibit cancer cell growth, inhibit proliferation of human endothelial cells in vitro. Moreover, UCN-01, at concentrations as low as 32 nM, prevent microve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…It is therefore likely that the cytostatic effect of UCN-01 in carcinomas with constitutively activated STAT3, for example, head and neck tumours (Patel et al, 2002) might be partly due to the inhibition of STAT3 phosphorylation and the resulting Bcl-x L suppression. Furthermore, the observed antiangiogenic effect of UCN-01 (Kruger et al, 1998) may also be due to the inhibition of STAT3, which was shown to mediate angiogenesis (Wei et al, 2003). In the investigated colon cancer cell lines, however, we detected neither constitutive STAT3 Tyr705 phosphorylation nor the regulation of Bcl-x L by IL-6-activated STAT3.…”
Section: Discussionmentioning
confidence: 72%
“…It is therefore likely that the cytostatic effect of UCN-01 in carcinomas with constitutively activated STAT3, for example, head and neck tumours (Patel et al, 2002) might be partly due to the inhibition of STAT3 phosphorylation and the resulting Bcl-x L suppression. Furthermore, the observed antiangiogenic effect of UCN-01 (Kruger et al, 1998) may also be due to the inhibition of STAT3, which was shown to mediate angiogenesis (Wei et al, 2003). In the investigated colon cancer cell lines, however, we detected neither constitutive STAT3 Tyr705 phosphorylation nor the regulation of Bcl-x L by IL-6-activated STAT3.…”
Section: Discussionmentioning
confidence: 72%
“…In comparison, in normal prostate epithelial cells and endothelial cells, IC50 of UCN-01 as low as 25-35 nM. 57,58 Like normal prostate cells, normal mammary epithelial cells are very sensitive to UCN-01 with an IC50 of 10 nM. UCN-01 inhibits proliferation of endothelial cells at lower concentrations than those that inhibit prostate cancer cells.…”
Section: Inhibitors Of Mitogenic Kinases and Autonomous Growthmentioning
confidence: 99%
“…UCN-01 inhibits proliferation of endothelial cells at lower concentrations than those that inhibit prostate cancer cells. 58 Rb is essential for UCN-01-mediated G 1 arrest in normal cells. 59 Rb status is also a determinant of response to high concentrations of UCN-01 in non-small cell lung carcinoma.…”
Section: Inhibitors Of Mitogenic Kinases and Autonomous Growthmentioning
confidence: 99%
“…84,95 Experimental therapeutics, such as flavopiridol and UCN-01, induce apoptosis in leukemia cells, 96,98 whereas some cancer cell lines including PC3 prostate cancer cell line are resistant. 84,[99][100][101] Nevertheless, flavopiridol induces DNA fragmentation in squamous cell carcinomas resistant to DNAdamaging drugs. 102 Inhibitors of the proteasome induce apoptosis [103][104][105] even in PC-3 cell line.…”
Section: Proapoptotic Drug-or Apoptosis-prone Cellsmentioning
confidence: 99%